“Putting a Face on It”: The Trouble with Storytelling for Social Justice in Music Education - Hess, Juliet (Philosophy of music education review, 2021)
Music educators and music education researchers often rely on the use of story when advocating for social change. We may use story to illustrate a need for resources, point to a systemic injustice, illustrate a need for policy change, or identify an exclusion. Allies often utilize stories of oppression to demonstrate the untenability of situations or dehumanization experienced by particular people or groups. Stories shared, in other words, typically describe difficult, oppressive, or traumatic situations that may accomplish advocacy or social change goals but may also inadvertently reinscribe oppressive relations. This paper considers several questions in relation to this practice: What does it do for dominant group members to hear stories of marginalization? How can telling stories ultimately reinscribe oppression? How could individuals who offer their stories benefit from sharing? What educational value does telling stories offer? If storytelling carries potential for reinscribing oppression, how else might educators advocate to meet the needs identified? To theorize this type of storytelling, I put Martin Buber's work on I-Thou in conversation with work of Homi Bhabha. Buber's theorizing allows the consideration of different types of relations, while Bhabha provides ways to explore the effects of what Buber terms an I-It relationship on individuals subject to systemic oppression. Ultimately, I explore ways to recenter minoritized voices and examine how it might be possible to consider oppressive systems without acquiescing to the demand for story.